Institutional strengthening of Pokdarwis Banyumili in utilizing the potential of water resources as tourism - Ronny Winarno; Vita Fibriyani; Ardhiwinda Kusumaputra (University of Merdeka Malang, 2025)
Kelompok Sadar Wisata (Pokdarwis) is an organization/institution whose purpose is to develop an area with tourism potential. The Bekacak area, Kolursari Village, Bangil Subdistrict, Pasuruan Regency, is one of the areas that Pokdarwis Banyumili sees as having tourism potential by utilizing water resources. However, these efforts have not yet run optimally because of the institutional aspect of Pokdarwis Banyumili. There are two main problems, namely human resource management and institutional governance. An effort is needed to strengthen Pokdarwis Banyumili as an institution/organization. The goal is for Pokdarwis Banyumili to become a strong institution, so that it can optimally develop the tourism potential in its area. Therefore, a community service program was carried out. The method used was through Focus Group Discussion (FGD) activities or training, which specifically provided benefits to increase the understanding of Pokdarwis Banyumili administrators/members. Materials, discussions, and simulations were provided on the topics of Pokdarwis institutional governance, environmental sustainability, tourism development, and building cooperation with other parties. Supported by digitalization by utilizing applications, social media, and websites. This can result in increased understanding and competence for the management/members of Pokdarwis Banyumili so that they can make it a strong and optimal institution in the tourism sector.